TRANSFORMASI PELABUHAN TANJUNG PRIOK DALAM MASYARAKAT EKONOMI ASEAN (MEA) - Desri Gunawan S; Glory Yolanda Yahya (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2018)
ASEAN Economic Community (MEA) makes an increase in intra- ASEAN trade, which requires excellent trade facilities. The main trade facility between countries is the port. Tanjung Priok is the main and largest port of Indonesia, how is readiness of this port in MEA. This research method using qualitative with data collection techniques from the literature and analysis of this research explanatory is to describe a phenomenon with actual facts that occur in the field and then analyze it. Rresult of this research is transformation of port Tanjung Priok to be effective and efficient such as INAPORTNET as Supporting the Implementation of National Single Window (NSW), Application of EDI (Electronic Data Interchange) System as Single Document at Tanjung Priok Port, implementing Information Communication Technology (ICT) system, Port Modernization, Improving the Quality of Human Resources and Establishing New Priok PortI. Conclusion of this research is that port of Tanjung Priok must be maintained and developed in order to remain the main port of Indonesia and upgraded to the International Hub Port.